(untitled) (International Journal of Innovative Technologies in Economy, 2026)
As institutional investors with long-term commitments, insurance companies are increasingly integrating environmental, social, and governance (ESG) criteria into their investment strategies. This paper explores the shift from a traditional risk-and-return optimization framework to a sustainability-focused model. Through a qualitative and comparative analysis, the study examines how ESG integration is transforming current industry practices and portfolio diversification strategies. It identifies the correlation between high ESG ratings and portfolio sustainability, investigating whether sustainable investing serves as a mechanism for optimization or a structural constraint. The research specifically addresses the interplay between ESG-driven asset allocation and regulatory frameworks, such as Solvency II, to evaluate impacts on capital requirements and risk mitigation. Ultimately, the study identifies ESG as a vital tool for enhancing investment portfolio resilience and managing long-term systemic risks within the evolving global regulatory landscape.